Clinical efficacy of sacubitril-valsartan combined with acute ST-segment elevation myocardial infarction after reperfusion: A systematic review and meta-analysis - Zhang, Dong; Wu, Hui; Liu, Di; Li, Yunzhao; Zhou, Gang; Yang, QingZhuo; Liu, YanFang (Frontiers in Cardiovascular Medicine, 2022)
Background Several studies have investigated the combined use of sacubitril- valsartan after reperfusion in acute ST-segment elevation myocardial infarction (STEMI). However, the sample sizes of these studies were small and their results were somewhat heterogeneous. To determine the effect of sacubitril-valsartan on myocardial ischemia-reperfusion. Methods Search PubMed, EMbase, Web of Science and The Cochrane Library, CNKI database, VIP database and Wanfang digital journal full-text database for eligible articles from their date of inception up to April, 2022. All data were meta-analyzed using Review Manager 5.3 and STATA 16.0 software. Results A total of 23 studies including 2,326 patients with acute STEMI were included. These results of this meta-analysis indicated that left ventricular ejection fractions (LVEF) value within 6 months after surgery (OR, 4.29; 95% confidence interval, 3.78–4.80; P < 0.00001), left ventricular end-diastolic diameter (LVEDD) value within 6 months after surgery (OR, −3.11; 95% CI, −3.87 to −2.35; P < 0.00001) and left ventricular end-diastolic volume (LVEDV) value 6 months after operation (OR, −6.22; 95% CI, −7.10 to −5.35; P < 0.00001) are better than without sacubitril and valsartan. Conclusion To sum up the above, the results of this study suggest that sacubitril- valsartan can reduce the reperfusion injury of ischemic myocardium by improving cardiac function within a follow-up period of 6 months.